Characterisation of the Utrerana Chicken Breed Farms in Spain - Antonio Plata-Casado; Carmelo García-Romero; Pedro González-Redondo (Animals)
With the aim to characterise the situation of the subsector, 25 poultry farms of the endangered native Utrerana chicken egg-laying-oriented breed (Gallus gallus Linnaeus, 1758) were surveyed in Andalusia (southern Spain) from 2021 to 2023 to investigate the structure of the farms, number of birds, health status, feeding management, and marketing of their products. It was found that the pace of foundation of Utrerana chicken farms accelerated from 2009, and most of the farms were concentrated in the province of Seville. Only 40% of the farms were legally registered. This breed is raised on small farms mainly dedicated to self-supply and raising birds for conformation and their aesthetic values, with limited marketing of eggs and meat, with facilities consisting often of one poultry house and one outdoor enclosure, and with a low number of laying hens per farm (53.5 on average). Current productivity is low, with an average of 139 eggs per hen per year, but hens have a long reproductive lifespan, averaging 4 years. The Partridge variety of the breed was the most common, followed by the Black-barred and Black varieties, while the White variety was very scarce, with only 31 specimens in total. Two-thirds of the farmers also raised other breeds of chickens, in addition to the Utrerana. The management and production system was free-range or backyard, with a certain proximity to the requirements of European Union-certified organic production with regard to stocking densities and generally with a good sanitary status, respect for welfare, and implementation of biosecurity measures on the farms. The feeding of the chickens was based on grazing in outdoor enclosures and on the provision of grains and compound feed, with 40.0% of farmers using commercial compound feed and half preparing feed themselves. Two-thirds of the farmers were affiliated with the National Association of Utrerana Chicken Breeders (“Asociación Nacional de Criadores de Gallinas Utreranas”, ANCGU, in Spanish); almost half of them took part with their birds in fairs and conformation shows, such as the Utrerana Chicken Fair held in Utrera (province of Seville) and more than a quarter of them have sold live birds of the breed at these fairs. The farmers carry out few promotional and advertising activities for their farms and products, predominantly by using social networks, and the market area reached is mainly local. In conclusion, this research has shown that the current alternative production system for Utrerana chicken is similar to that of the hens that originated the breed and consists of a few amateur farms, with a small number of birds, distributed mainly throughout the Andalusian countryside. It has been highlighted that there is a need for the livestock authorities to implement programmes for supporting farmers and promoting the breeding of this endangered avian breed, native to the Spanish zoogenetic heritage.